Significant abundance of bacterial flagellin and expression of its surface localized receptor toll-like receptor 5 and cytokine interleukin-22 in South African infants with poor oral rotavirus vaccine take - Nontlantla J. Haindongo; Mapaseka Seheri; Cliff A. Magwira (Gut Pathogens)
Abstract Bacterial flagellin, a potent intestinal innate immune activator, prevents murine rotavirus (RV) infection independent of adaptive immunity and interferons. The flagellin-induced immunity is mediated by Toll-like receptor (TLR5) and Nod-like receptor C4 (NLRC4), which elicit the production of interleukins 22 (IL-22) and IL-18, respectively. Here, we assessed whether a high abundance of flagellin at the time of vaccination would negatively affect the oral RV vaccine take. Fecal samples were collected from infants a week after first dose of Rotarix vaccination to establish vaccine shedders (n = 50) and non-shedders (n = 44). The abundance of flagellin and expression of flagellin-encoding fliC, TLR5 and NLRC4, IL-22 and IL-18 genes was determined by qPCR. There were no differences in the abundance of flagellin between vaccine shedders and non-shedders (p = 0.15). However, the expression of FliC was increased 7.5-fold in non-shedders versus shedders (p = 0.001). Similarly, TLR5 (p = 0.045), and not NLRC4 (p = 0.507,) was significantly expressed in non-shedders versus shedders. The expression of IL-22 (p = 0.054), and not IL-18 dependent NLRC4 (p = 0.650), was increased 3.4-fold in non-shedders versus shedders. Collectively, our observations suggest a possible negative impact of the abundance of viable flagellated bacteria at the time of vaccination on the replication and therefore the performance of RV vaccines.